"Everything's technology now": the role of technology in home- and school-based summer learning activities in Canada. Issue 2 (3rd April 2021) - Rizk, Jessica; Hillier, Cathlene
ABSTRACT: Though summer learning loss has been widely documented across both the United States and Canada, there is little knowledge on how parents and teachers view the use of technology in the context of summer vacation, and what the role of digital tools are in potentially alleviating achievement gaps due to summer learning loss. Drawing on 71 parent and 37 teacher interviews from a large-scale Canadian study examining summer learning loss in Ontario through summer literacy and numeracy programs for students (grades 1–3), this study highlights the complexities associated with using digital tool in both home and school life in the summer. Through extensions of Bourdieu's theory of cultural capital, we suggest that digital tools are becoming a new type of valued skillset that parents and educators are acknowledging. In specific, our main findings center around three interrelated themes: i) comfort with technology; ii) home-school connections; and iii) perception of children as digital natives. Results may be fruitful for parents, educators, and policymakers to understand the larger role that digital technology plays amongst Canadian families and teachers during the summer months and school year. Capturing these discussions can maximize both school and home use of digital tools.